Development of an Adaptive Enrichment Module Aligned with the Learning Outcomes of the Kurikulum Merdeka - Sirry Alvina; Henni Fitriani; Nisa Fazria Mauliza; Ucia Mahya Dewi (Electronic Journal of Education, Social Economics and Technology, 2025)
This research aims to develop an enrichment module on chemistry materials in class XI odd semesters that are in accordance with the principles of the kurikulum merdeka. Development is carried out using the Research and Development (RD) model from Borg and Gall which is simplified into eight stages, including needs analysis, design, expert validation, teacher feasibility test, and student response. The results of validation by subject matter experts showed a validity rate of 86% (very valid category), while validation by media experts reached 91.42%. The feasibility test by the teacher obtained a score of 92.35%, and the students' response showed an acceptance rate of 84.56% (the category strongly agreed). These findings show that the enrichment modules developed are not only feasible and valid in terms of content and appearance, but also effective in supporting independent learning and improving students' understanding of chemical concepts. Thus, this enrichment module has proven to be effective and applicable as additional teaching materials in chemistry learning based on the kurikulum merdeka. This module can facilitate students in understanding the material in a more in-depth and structured way, as well as encourage independent learning. In addition, this module can also function as a solution to the limitations of contextual and systematic teaching materials in the school environment. Therefore, the results of this research are expected to be a real contribution in efforts to improve the quality of education, especially in the development of learning media that are adaptive to curriculum changes.